2017
DOI: 10.1002/mp.12049
|View full text |Cite
|
Sign up to set email alerts
|

Fast and robust multimodal image registration using a local derivative pattern

Abstract: Purpose: Deformable multimodal image registration, which can benefit radiotherapy and image guided surgery by providing complementary information, remains a challenging task in the medical image analysis field due to the difficulty of defining a proper similarity measure. This article presents a novel, robust and fast binary descriptor, the discriminative local derivative pattern (dLDP), which is able to encode images of different modalities into similar image representations. Methods: dLDP calculates a binary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…The registration process by combining the structural images, such as CT or MRI images, with functional images, such as PET or SPECTis used in different applications such as disease diagnosis and computer-aided surgery [16][17][18][19]. Combined information from the variability of images, for instance, Computer tomography (CT), is applied to obtain more comprehensive data about the patient.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…The registration process by combining the structural images, such as CT or MRI images, with functional images, such as PET or SPECTis used in different applications such as disease diagnosis and computer-aided surgery [16][17][18][19]. Combined information from the variability of images, for instance, Computer tomography (CT), is applied to obtain more comprehensive data about the patient.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…Various machine learning-based methods [41][42][43][44][45][46][47] for image registration have proposed by investigators to not only align the anatomical structures but also alleviate the appearance difference. Hu et al [41] proposed a method based on regression forest for image registration of two arbitrary MR images.…”
Section: Reconstruction Of 7 T-like Mr Image From 3 T Mr Image 3 T Mmentioning
confidence: 99%
“…The results showed that such an approach like CNN-based model can significantly outperform other state-of-the-art methods. Jiang et al [43] employed a discriminative local derivative pattern method to achieve fast and robust multimodal image registration. The results revealed that the proposed method can achieve superior performance regarding accuracy in multimodal image registration as well as also indicated the potential for clinical US-guided intervention.…”
Section: Reconstruction Of 7 T-like Mr Image From 3 T Mr Image 3 T Mmentioning
confidence: 99%
“…In the FastMI registration, 3 D-FAST was performed using 90 neighborhoods with a 3 Â 3 Gaussian filter mask and a threshold of M ¼ 0.1 in Equation (10). The window's width of structural distance q u in Equation (13) is set to be 20.…”
Section: Accuracy Experiments On 3 D Imagesmentioning
confidence: 99%
“…For example, Wachinger et al [7] transformed multi-modal images into entropy or Laplacian images. Heinrich et al [8,9] and Jiang et al [10,11] transferred multi-modal images to unimodal images with local structure descriptor named 'Modality Independent Neighborhood Descriptor' (MIND), 'Self-Similarity Context' (SSC), 'discriminative Local Derivative Pattern' (dLDP) and 'modality independent Local Binary Pattern' (miLBP). Although methods in this category have higher registration speed, they may not be applicable for some tissues or organs with less structural information and the modality transformation may lose a large amount of image information.…”
Section: Introductionmentioning
confidence: 99%